In situ measurement of the strains within a mechanically loaded polygranular graphite - Marrow, T; Liu, D; Barhli, S; Vertyagina, Y; Collins, D; Reinhard, C; Kabra, S; Flewitt, P; Smith, D; Saucedo Mora, L (Elsevier, 2016)
Neutron diffraction and synchrotron X-ray diffraction and imaging have been applied to study, in situ, the mechanical response to tensile and bending loading of polygranular Gilsocarbon nuclear grade near-isotropic graphite (grade IM1-24). Digital image correlation of X-ray radiographs and digital volume correlation of tomographs allow measurement of bulk elastic moduli and examination of the heterogeneity of deformation in the microstructure. Both the neutron and X-ray studies show the application of tensile strain reduces the bulk elastic modulus. A permanent set is observed to develop with applied tensile strain. The elastic strains within the graphite crystals were measured by diffraction; a cross-correlation analysis method has been applied for greater speed, robustness and improved precision in the measurement of the change in basal plane separation distance. In compression, a linear relation is observed between the elastic strains in the graphite crystals and the applied strain. In tension, this relationship is non-linear. The results are discussed with respect to the distribution of elastic and inelastic strain within the graphite microstructure. It is deduced that the significant residual elastic strains in the as-manufactured graphite are relaxed by microcracking as tensile strain is applied.